A comparison of the severity of substance use disorder in patients with natural opium use versus heroin use - Mukesh Kumar Swami; Siddharth Sarkar; Naresh Nebhinani; Roshan Bhad; Surendra Singh Rajpurohit; Esha Sood; Pranshu Singh; Raja Babu Ramawat; Ashwani Kumar Mishra (Indian Journal of Psychiatry)
Background: Historically and culturally, natural opium is considered less harmful in comparison to heroin/pharmaceutical opioids, but the evidence regarding this is limited and mostly indirect. Aim: The aim of this analysis was to compare problems experienced by patients with natural opium and heroin use. Methods: The study is a secondary analysis of data collected during the development of the Assessment of Severity of Substance use for Outcomes Research and Treatment (ASSORT) scale. Patients with natural opium use (n = 72) and heroin use (n = 172) were compared. Results: Natural opium users were of higher age and from a rural background. The ASSORT score was significantly lower among natural opium users than heroin users (mean 77.8 versus 99.7, P < 0.001). Natural opium users experienced fewer problems in all domains of ASSORT except problems in physical health. Conclusion: Hence, patients with natural opium use experience fewer problems in comparison to those with heroin use.